Hubungan Tingkat Pengetahuan terhadap Keterampilan Kader dalam Pengukuran Tinggi Badan dan Berat Badan Balita di Posyandu Cikarang Selatan - Dzandini, Putri Budianingsih; Alamsah, Deni; Asmi, Nur Fauzia; Nurpratama, Widya Lestari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Inaccuracies in anthropometric measurements of toddlers caused by improper positioning are a significant issue that can hinder early detection of stunting and other nutritional problems. This study aims to evaluate the relationship between cadres' length of service and knowledge level with their skills in performing anthropometric measurements of toddlers in the Cikarang Selatan area. This study was conducted using a quantitative approach. The design used for this study was cross-sectional. 41 cadres who met the inclusion criteria were included in the working area of Cikarang Selatan Subdistrict, specifically in Pasirsari Village, Bekasi Regency. Data analysis was conducted using the chi-square test to examine relationships between variables. The analysis showed that cadre knowledge was also significantly associated with the skill of measuring height (p-value = 0.000; OR = 45.500). However, the relationship between knowledge and the skill of measuring weight did not reach statistical significance (p-value = 0.120; OR = 2.963). The findings of this study indicate that cadre knowledge has a significant effect on the skill of measuring height. Conversely, knowledge was not proven to have a significant relationship with the skill of measuring weight. Cadres with adequate knowledge tend to have better skills in measuring both the height and weight of toddlers.